Profesionální pomáhání Rozhovory napříč pomáhajícími profesemi - Švec, Vlastimil (Reflexe, 2019)
Title in English: Professional helping: Interviews across helping professions. The book introduces various helping professions. It presents reflections of helping professionals in their professions as well as on helping. The book reveals the core of helping professions, requirements for being helping professionals and act as helping professionals. It is an introduction to the word, where helping is the key issue.